Freedom in learning from family education perspective in covid 19 pandemic - Fatmi Fauzani Duski; Firman Firman; Rusdinal Rusdinal (Indonesian Institute For Counseling, Education and Therapy, 2020)
In the era of pandemic covid 19, families become the most important tool in developing children's creativity. With the concept of